Mullerian and gonadal dysgenesis: an unusual presentation - Mehrotra, Ragini; Tyagi, Kamini; Yadav, Amita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
The estimated prevalence of a unicornuate uterus is rather low, approximately 0.3% of the whole population, 0.6% of the infertile population, and 0.2% of the fertile population. Of the mullerian defects, however, unicornuate uterus is found in 3 to 13% of women. Ovarian maldescent occasionally occurs in patients with a normal uterus, the incidence is reported to be 20% when the uterus is absent (Rokitansky-Kustner - Hauser syndrome) and as high as 42% in cases of unicornuate uterus. The occurrence of Mullerian anomalieswith concomitant gonadal developmental abnormalities isvery rare. Case reports about the unicornuate uterus withovarian abnormalities are very limited in the literature. We present a case of 17 year old girl with primary amenorrhoea and hematometra, for which she was operated and later on she was diagnosed as a case of vaginal and cervical atresia with unicornuate uterus together withipsilateral ovarian agenesis and contralateral ectopic ovary.